IMPROVEMENT OF THE METHODOLOGY OF PHYSICAL TRAINING OF CADETS OF THE WESTERN MILITARY DISTRICT WITH SPECIFIC TRAINING CONDITIONS OF THE MINISTRY OF INTERNAL AFFAIRS OF UKRAINE - Andrii Zabora; Oleg Kamaev (Kharkiv State Academy of Physical Culture, 2021)
Purpose: to develop and experimentally substantiate the improved methodology of physical training of cadets. Material and methods: the study was carried out at the educational and sports base of the KhNUIA. The study involved 46 cadets from two academic groups of the second year of study. Experimental (n-24) and control (n-22) groups were created. The experiment continued throughout the fourth semester. The following research methods were used in the work: analysis and generalization of scientific and methodological information, pedagogical observation, testing, pedagogical experiment, methods of mathematical statistics. Results: due to the use of the experimental methodology, selection of means and methodology of complex exercises fulfillment, an increase in the indices of physical and special readiness of cadets was obtained. Conclusions: the methodology of physical fitness improvement was developed; it provided a reliable improvement of cadets' physical readiness indices, contributes to the successful mastering of self-defense tactics exercises.